Metagenomic Insights Into the Mechanisms for Biodegradation of Polycyclic Aromatic Hydrocarbons in the Oil Supply Chain - Hidalgo, Kelly J.; Sierra-Garcia, Isabel N.; Dellagnezze, Bruna M.; de Oliveira, Valéria Maia (Frontiers in Microbiology, 2020)
Petroleum is a very complex and diverse organic mixture. Its composition depends on reservoir location and in situ conditions and changes once crude oil is spilled into the environment, making the characteristics associated with every spill unique. Polycyclic aromatic hydrocarbons (PAHs) are common components of the crude oil and constitute a group of persistent organic pollutants which are easily accumulated in soil and sediment due to their low solubility and high hydrophobicity. The process by which oil is sourced and made available for use is referred to as the oil supply chain and involves three parts: 1) upstream, 2) midstream and 3) downstream activities. As consequence from oil supply chain activities, crude oils are subjected to biodeterioration, acidification and souring, and oil spills are frequently reported affecting not only the environment, but also the economy and human resources. Different bioremediation techniques based on microbial metabolism, such as bioaugmentation, biostimulation and natural attenuation are promising approaches to minimize the environmental impact of oil spills. The rate and efficiency of this process depend on multiple factors, like pH, oxygen content, temperature, concentration and availability of the contaminants and type and abundance of microorganisms present in the affected (polluted) area. Emerging approaches, such as (meta-)taxonomics and (meta-)genomics bring new insights into the molecular mechanisms of PAH microbial degradation at both single species and community levels in oil reservoirs and groundwater/seawater spills. We have scrutinized the microbiological aspects of biodegradation of PAHs naturally occurring in oil upstream activities (exploration and production), and crude oil and/or by-products spills in midstream (transport and storage) and downstream (refining and distribution) activities. This work addresses PAH biodegradation in different stages of oil supply chain affecting diverse environments (groundwater, seawater, oil reservoir) focusing on genes and pathways as well as key players involved in this process. In depth understanding of the biodegradation process will provide/improve knowledge for optimizing and monitoring bioremediation in oil spills cases and/or to minimize/impair the degradation in reservoirs avoiding deterioration of crude oil quality.